Learning Skills of Junior High School - Baspuri Luahambowo; Daharnis Daharnis; Yeni Karneli (International Journal of Applied Counseling and Social Sciences, 2019)
Learning skills is demands that must be possessed by students to achieve maximum learning outcomes. This study aims to reveal the picture of students' learning skills in junior high school 25 Padang state. This research uses the quantitative approach with descriptive analysis method. The sample consisted of 31 students of class VIII selected at random. The instrument used is a learning skill questionnaire with a reliability of 0.754. The results showed that the students' learning skill was in the high category with an average score of 144 with the achievement level of 76%.